2007
DOI: 10.1016/j.ajog.2007.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Posterior repair and sexual function

Abstract: OBJECTIVE-The purpose of this study was to determine the effect of posterior repair (PR) on sexual function in patients who have undergone incontinence and/or pelvic reconstructive surgery.STUDY DESIGN-A cohort study of women who underwent incontinence and/or prolapse surgery was performed. Participants completed the pelvic organ prolapse urinary incontinence sexual questionnaire (PISQ) before and after the operation. PISQ scores were compared between women who underwent PR and women who did not. RESULTS-Of 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 18 publications
4
43
0
5
Order By: Relevance
“…Alternatively, the association between pelvic floor disorders and certain aspects of female sexual function may suggest a common etiology, such as pelvic muscle weakness or decreased urogenital sensation. Recent studies suggesting that surgical treatment for pelvic floor disorders may improve sexual function (18,19), but the impact of treatment on sexual function has not been consistently reported (20). Thus, further research is needed to clarify whether certain treatments for pelvic floor disorders are more effective than others in restoring sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the association between pelvic floor disorders and certain aspects of female sexual function may suggest a common etiology, such as pelvic muscle weakness or decreased urogenital sensation. Recent studies suggesting that surgical treatment for pelvic floor disorders may improve sexual function (18,19), but the impact of treatment on sexual function has not been consistently reported (20). Thus, further research is needed to clarify whether certain treatments for pelvic floor disorders are more effective than others in restoring sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study evaluating patients undergoing prolapse repair found that the proportion of patients reporting dyspareunia did not change among those with posterior repair, but among those who did not undergo posterior repair, the proportion with dyspareunia decreased significantly. 13 In a meta-analysis of prolapse repairs using mesh, dyspareunia was reported at approximately 10% postoperatively. 14 …”
Section: Prolapse and Sexual Healthmentioning
confidence: 99%
“…Pese a que no era objetivo del estudio comparar la función sexual de acuerdo a los procedimientos quirúrgicos efectuados, este porcentaje de mujeres con dispareunia pudiera estar asociada a la realización de la colporrafia posterior (12,(26)(27)(28)(29). Asimismo, Pauls y cols (22), encontraron que antes de la reparación el abultamiento vaginal era la principal barrera para la actividad sexual, resultado que coincide con el alto porcentaje de mujeres de este estudio que manifestaban esta misma queja (76,6%).…”
Section: Discussionunclassified